'I was like, just wow!': insights from Global Englishes teacher professional development. Issue 3 (2nd September 2022) - Prabjandee, Denchai; Fang, Fan (Gabriel)
ABSTRACT: The global spread of English presents a multitude of challenges for teachers who must instruct learners differently to help them use English with a variety of people in multilingual contexts. However, prior research has largely ignored the question of how to support teachers to tackle these challenges. This study attempts to provide teacher professional development for implementing Global Englishes Language Teaching (GELT). An explanatory mixed-methods research design was used to document the effects of a teacher professional development program received by teachers. The findings showed that teachers reported having increased knowledge of GELT, slightly changed attitudes toward GELT, and ambivalently improved skills for implementing GELT. Four aspects of the professional development contributed to these changes: practical, experiential, theoretical, and inspirational. Implications for providing GELT teacher professional development were also discussed.